Multiferroicity in B-site ordered double perovskite Y2MnCrO6 - 房勇 颜士明 乔文 王伟 王敦辉 都有为 (中国物理B：英文版, 2014)
Double perovskite manganite Y2MnCrO6 ceramic Novel multiferroic properties are displayed with respect is synthesized and its multiferroic properties are investigated. to other multiferroics, such as high ferroelectric phase transi- tion temperature, and the coexistence of ferrimagnetism and ferroelectricity. Moreover, the ferroelectric polarization of Y2MnCrO6 below the magnetic phase temperature can be effectively tuned by an external magnetic field, showing a re- markable magnetoelectric effect. These results open an effective avenue to explore magnetic multiferroics with spontaneous magnetization and ferroelectricity, as well as a high ferroelectric transition temperature.